2008
DOI: 10.1182/blood-2008-05-153445
|View full text |Cite
|
Sign up to set email alerts
|

TINF2 mutations result in very short telomeres: analysis of a large cohort of patients with dyskeratosis congenita and related bone marrow failure syndromes

Abstract: Dyskeratosis congenita (DC) is a multisystem bone marrow failure syndrome characterized by a triad of mucocutaneous abnormalities and a predisposition to cancer. The genetic basis of DC remains unknown in more than 60% of patients. Mutations have been identified in components of the telomerase complex (dyskerin, TERC, TERT, NOP10, and NHP2), and recently in one component of the shelterin complex TIN2 (gene TINF2). To establish the role of TINF2 mutations, we screened DNA from 175 uncharacterised patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
311
2
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(336 citation statements)
references
References 26 publications
12
311
2
7
Order By: Relevance
“…Savage et al 7 described a case of CRMCC who died after BMT; however, detailed information on the conditioning regimen was not available. Walne et al 8 also described four cases of CRMCC with a TINF2 mutation, of which one received BMT, but details on the conditioning regimen and transplantation courses were not reported. In DKC, circulating lymphocytes and fibroblasts exhibit an increased in vitro sensitivity to radiation and alkylating agents.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Savage et al 7 described a case of CRMCC who died after BMT; however, detailed information on the conditioning regimen was not available. Walne et al 8 also described four cases of CRMCC with a TINF2 mutation, of which one received BMT, but details on the conditioning regimen and transplantation courses were not reported. In DKC, circulating lymphocytes and fibroblasts exhibit an increased in vitro sensitivity to radiation and alkylating agents.…”
mentioning
confidence: 99%
“…7 Mutated amino acids were tightly clustered in the position between 280 and 290 in classic DKC or CRMCC patients. 7,8 On the basis of these findings, a diagnosis of CRMCC was made. At the age of 17 months, the exudative retinopathy was successfully treated with laser coagulation, pars plana vitrectomy and the intra-vitreal administration of vascular endothelial growth factor inhibitors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Autosomal dominant forms of DC are caused by mutations in TERT, TERC or the telomere binding protein TIN2, providing a clear link between telomere shortening and the pathophysiology of DC. [13][14][15][16] Several dedicated cofactors associate with dyskerin and are required for telomerase RNP assembly and function. Many of these, such as NAF1, pontin and reptin, aid in RNP assembly but do not remain associated with the mature telomerase enzyme.…”
mentioning
confidence: 99%
“…More than 30 such cases have been described, and recent studies showed that patients with HH have very short telomeres. Several patients with HH have now been found to have mutations in DC genes proven to cause DC, including DKC1, TINF2, or TERT [16][17][18].…”
Section: Clinical Featuresmentioning
confidence: 99%